Paraneoplastic cerebellar degeneration and limbic encephalitis in a patient with adenocarcinoma of the colon. - Tsukamoto, T (1993)
The rare association of two neurological paraneoplastic syndromes, paraneoplastic cerebellar degeneration and limbic encephalitis occurred in a 55 year old woman with a microscopic adenocarcinoma in a colonic polyp. Complete removal of the tumour by polypectomy brought about a favourable recovery from limbic encephalitis but the cerebellar ataxia remained. High titres of antineuronal nuclear antibody resembling anti-Hu were demonstrated in serum by immunohistochemistry using rat brain as a substrate. The antibody identified a protein band of 41 kDa on a Western immunoblot.